HUBUNGAN POLA ASUH ORANG TUA DENGAN PERILAKU BULLYING ANAK DI INDONESIA: STUDI CROSS-SECTIONAL : Relationship between Parenting Patterns and Bullying Behavior of Children in Indonesia: A Cross-Sectional Study - Dhian Satya Rachmawati; Lela Nurlela; Sukma Ayu Candra Kirana; Iis Fatimawati; Bayu Krisna Alriyanto; Ali Sairozi (Journal of Community Mental Health and Public Policy, 2023)
ABSTRACT Background: Children are the next generation for a bright and better future. Often there is bullying among children at school. Bullying has become a global problem, especially in the school environment. Bullying has a big impact on children, thus, bullying behavior must be prevented. Purpose: The purpose of this study was to analyze the relationship between parenting style and bullying behavior at the Balong Tani Jabon Public Elementarz School, Sidoarjo. Methods: The design of this research is correlational analysis. The population of the students at grades 4-6 was 130 children. The sampling technique used was proportionate stratified random sampling with a total sample of 98 school-age children grades 4-6. The independent variable was parenting style. The dependent variable was bullying at the school. The instrument used was a questionnaire on parenting and bullying behavior. Association was statistically tested using Spearman Rho. Result: From 98 respondents 66 respondents (67.3%) had democratic parenting patterns, and 87 respondents had non-bullying behavior (88.8%). The Spearman rho test resulted in a p value = 0.004 meaning that there was an association between parenting styles and bullying behavior at the school. The correlation coefficient of the association was 0.287 meaning that the relationship between the two variables was weak. Conclusion: The presence of both parents in a harmonious family is important so that they can share roles in caring for their children and can spend time together to form a democratic parenting pattern, in order to form children to become good individuals and do not engage in bullying behavior. ABSTRAKLatar Belakang: Anak adalah generasi penerus untuk masa depan yang cerah dan lebih baik Seringkali ada perilaku bulliying anak di sekolah. Bullying sudah menjadi masalah global terutama di lingkungan sekolah. Bullying mempunyai dampak yang besar bagi anak – anak untuk itu perilaku bullying harus di cegah. Tujuan: Tujuan penelitian ini menganalisis hubungan pola asuh orang tua dengan perilaku bullying di SD Negeri Balong Tani Jabon Sidoarjo. Metode: Desain pada penelitian ini analitik korelasional. Populasi anak usia sekolah di SD Negeri Balong Tani kelas 4-6 sebanyak 130 anak, Teknik sampling menggunakan proportionate stratified random sampling didapatkan sampel 98 anak usia sekolah kelas 4-6 di SD Negeri Balong Tani. Variabel bebas adalah pola asuh orang tua. Variabel terikat adalah bullying di SD Negeri Balong Tani, Instrument yang digunakan adalah kuesioner pola asuh dan perilaku bulliying. Uji statistik hubungan menggunakan Spearman Rho. Hasil: Hasil penelitian dari 98 responden di SD Negeri Balong Tani, didapatkan data pola asuh demokratis sebanyak 66 responden (67,3 %), Perilaku bukan bullying sebanyak 87 responden (88,8 %). Hasil uji Spearman rho didapatkan nilai p = 0,004 artinya terdapat hubungan antara pola asuh orang tua dengan perilaku bullying di SD Negeri Balong Tani. Hasil analisa didapatkan koefisien korelasi 0,287 artinya hubungan kedua variabel bersifat lemah. Kesimpulan: Kehadiran kedua orang tua yang lengkap dalam keluarga yang harmonis penting agar dapat berbagi peran dalam mengasuh anaknya dan bisa saling mengisi waktu bersama membentuk pola asuh demokratis, sehingga anak menjadi pribadi yang baik dan tidak melakukan perilaku bullying.